Pay in Europe in the 21st century - Aumayr - Pintar, Christine; Cabrita, Jorge; Fernandez - Macias, Enrique; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2014)
The issue of wages has attracted particular attention at European level since the onset of the economic crisis. Changes in economic governance, notably within the European Semester, have prompted discussions on wage - setting mechanisms. While, overall, wage-bargaining regimes have remained relatively stable over time in many countries, the most substantial changes were seen in Member States facing more difficult economic circumstances.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Compensation management -- European Union countries; Wage payment systems -- European Community countries; Electronic books